The great retreat Napoleon's Grande Armée in Russia : the contingents and the artefacts - Korolev, Aleksandr 1966- (Unicorn Press Ltd., 2014)
The Great Retreat: Napoleon's Grande Armee in Russia is a remarkable new record of one of history's most famous military campaigns. In 1812, no fewer than 570,000 troops from 19 countries battled for the soul of Europe of the 450,000 men to cross the River Nieman in June 1812, only about 60,000 returned.